Charge separated states and singlet oxygen generation of mono and bis adducts of C60 and C70 - Dallas, P; Rogers, G; Reid, B; Taylor, RA; Shinohara, H; Briggs, GAD; Porfyrakis, K (Elsevier, 2015)
We present a series of fullerene derivatives and a study on their photoluminescence properties, complete with their efficiency as singlet oxygen generation photosensitizers. We demonstrate the intramolecular charge transfer between pyrene donor and fullerene acceptor. The opposite effect in decay lifetime measurements is observed for the mono and bis adducts of C60 and C70 for the first time, indicating an interplay between charge-separation and locally excited states. A monoexponential decay was observed for the mono adduct of C60 and the bis adduct of C70, while a biexponential decay was observed for the bis adduct of C60 and the mono adduct of C70. The effect of these molecules as sensitizers of the singlet oxygen radical was tested using detailed 3D excitation photoluminescence maps. A quenching of the singlet oxygen for the C60-mono and C70-bis adducts was observed while a strong photosensitizing effect was observed for the C60-bis and C70-mono adducts.